OPTIMALISASI PEMBUKUAN MELALUI APLIKASI SI APIK DAN PEMANFAATAN E-COMMERCE SHOPEE SEBAGAI WUJUD DI DIGITAL MARKETING BAGI PELAKU UMKM RUMAH ANYAMAN BERAKIT - Hendy Satria; Marina Lidya; Novi Chandra Saputra; Meidi Yanto; Rezario Febrianta (Bajang Institute, 2025)
In the ever-evolving digital era, Micro, Small and Medium Enterprises (MSMEs) in Indonesia are faced with multiple challenges in financial management and marketing. Despite MSMEs' contribution to Gross Domestic Product (GDP) reaching around 60% and absorbing more than 97% of the workforce, many of them still rely on error-prone manual record-keeping. To overcome this obstacle, Bank Indonesia developed the SiApik application, which aims to assist MSMEs in making financial reports according to accounting standards. In addition, e-commerce platforms such as Shopee provide opportunities for MSMEs to expand their market reach. However, the adoption rate of SiApik and Shopee applications among MSMEs is still low, due to a lack of understanding and limited human resources in the use of digital technology. This research focuses on community service conducted at the Berakit Wicker House, where the KKN team provided training on the use of the SiApik and Shopee apps. The results showed significant improvements in the business owners' financial management and digital marketing capabilities. It is hoped that this program can improve the financial management professionalism of MSMEs, which in turn supports business sustainability and growth in the future.